2004
DOI: 10.1074/jbc.m402051200
|View full text |Cite|
|
Sign up to set email alerts
|

CEACAM6 Cross-linking Induces Caveolin-1-dependent, Src-mediated Focal Adhesion Kinase Phosphorylation in BxPC3 Pancreatic Adenocarcinoma Cells

Abstract: Despite lacking transmembrane or intracellular domains, glycosylphosphatidylinositol-anchored proteins can modulate intracellular signaling events, in many cases through aggregation within membrane "lipid raft" microdomains. CEACAM6 is a glycosylphosphatidylinositol-linked cell surface protein of importance in the anchorage-independent survival and metastasis of pancreatic adenocarcinoma cells. We examined the effects of antibody-mediated cross-linking of CEACAM6 on intracellular signaling events and anchorage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 61 publications
3
51
1
Order By: Relevance
“…Recently, the increase in anoikis susceptibility of CEACAM6-expressing human pancreatic carcinoma cells produced by CEACAM6 siRNA gene silencing was shown to be associated with an increase in caspase-8 and -3 activities (Duxbury et al, 2004). Our findings indicate that, in the case of CEA expression, there is also an associated caspase-mediated anoikis resistance, since we observed a partial inactivation of caspase-3 (Figure 1c) which correlated with anoikis inhibition by CEA (Figure 1a).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Recently, the increase in anoikis susceptibility of CEACAM6-expressing human pancreatic carcinoma cells produced by CEACAM6 siRNA gene silencing was shown to be associated with an increase in caspase-8 and -3 activities (Duxbury et al, 2004). Our findings indicate that, in the case of CEA expression, there is also an associated caspase-mediated anoikis resistance, since we observed a partial inactivation of caspase-3 (Figure 1c) which correlated with anoikis inhibition by CEA (Figure 1a).…”
Section: Discussionsupporting
confidence: 62%
“…In the case of anoikis inhibition, although it is well documented that CEA/CEACAM6 expression can inhibit the anoikis of human colorectal carcinoma cells (Ordonez et al, 2000;Soeth et al, 2001) and human pancreatic carcinoma cells (Duxbury et al, 2004), an effect that it is not produced by the transmembraneanchored CEA-family member CEACAM1 or the GPIanchored variant of the immunoglobulin superfamily member adhesion molecule, NCAM, (Ordonez et al, Molecular mechanism of CEA-mediated anoikis inhibition M del Pilar Camacho-Leal and CP Stanners 2000), the molecular mechanism implicated in this inhibitory effect was unclear. This study was focused on the molecular mediators associated with the anoikis resistance conferred by CEA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we found that overexpression of CEACAM6 downregulated Src activity and that the Src-selective inhibitor PP2 can disturb the cytoskeleton and interfere with adenovirus infection. This is contrary to a previous report that CEACAM6 cross-linking increased Src activity (28). It is known that several GPI-anchored proteins, including CEACAM family members, have no transmembrane or intracellular domains, but they are still able to modulate intracellular signaling events and to influence cell activities.…”
Section: Ceacam6 Is a Glycosylphosphatidylinositol-linked (Gpi-linked)contrasting
confidence: 55%
“…There is accumulating evidence that CEACAM6 has functional importance in tumorigenesis, including disrupting tissue architecture and affecting cell polarity, differentiation, anti-anoikis activity, tumor invasion, metastasis, and even chemoresistance (17,19,20,22,27,28). Inhibition of CEACAM6 expression by RNA interference or antibody targeting can inhibit tumor adhesion, growth, invasion, and metastasis, resulting in improved survival of mice with metastases (18,29,30).…”
Section: Ceacam6 Is a Glycosylphosphatidylinositol-linked (Gpi-linked)mentioning
confidence: 99%